International investment arbitration: winning, losing and why - Susan D. Franck (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
This Perspective reviews recent empirical research about investment treaty arbitration in order to help create a more accurate framework for policy choices and dispute-resolution strategies.
Keywords: 330